Analisis Peran Kewirausahaan dalam Meningkatkan Pendapatan Masyarakat - Maria Natalia Serci Leda; Esmeralda Manek; Florencia Virginia Nai Boro; Melania Bahi; Enike Tje Yustin Dima; Mariane Kauk; Maria Natalia Sulastri (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to analyze the role of entrepreneurship in increasing community income and strengthening local economic resilience. The research employed a qualitative approach, with data collected through interviews, observation, and documentation to obtain an in-depth understanding of entrepreneurial practices in the community. The informants were micro and small business actors selected using purposive sampling based on their involvement in income-generating business activities. The findings show that entrepreneurship has a significant role in improving community income. This is reflected in the increase in income after running a business, both in terms of amount, regularity, and household financial stability. Entrepreneurship also contributes to creating employment opportunities, reducing dependence on formal jobs, encouraging economic independence, and supporting local economic growth through the development of community-based businesses. However, several obstacles remain, including limited capital, inadequate managerial and technical skills, limited market access, low use of digital technology, and weak business networks. Therefore, support from government, financial institutions, educational institutions, and community organizations is needed to optimize entrepreneurship as a strategy for improving community welfare sustainably across diverse social and regional contexts in Indonesia.